Evaluating linkage between operators’ satisfaction and potential of local resources for rural tourism: Evidence from Matsuura in Japan - Ohe, Yasuo; Kurihara, Shinichi; Shimoura, Shinpei (Applied Studies in Agribusiness and Commerce, 2010)
As rural tourism evolves into diversification, the connection between the individual and local resource management is becoming an important issue for the sustainable evolution of rural tourism. To explore this point, we investigated conceptually and empirically whether rural tourism operators’individual satisfaction enhances utilization of local resources and, if so, what mechanism works for it by focusing on rural tourism accompanied by an educational program, i.e. a farm-stay with farm and rural experience services implemented as a part of school trips in Matsuura, Japan. From statistical tests and an econometric estimation based on a questionnaire survey of rural tourism operators we found that operators’individual satisfaction gained from interchange with visitors and direct feedback can positively enhance locally exerted effects that stimulate operators to recognize opportunities within their community and raise the potential for local resource use. Thus, we should strengthen this connection to eventually create a new viable activity.